ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MENGERJAKAN SOAL MATERI TEOREMA PHYTAGORAS PADA SISWA SMP KELAS VIII - Rinda Sari (LPD IKIP PGRI Pontianak, 2023)
Abstract: This study aims to describe and analyze students' creative thinking abilities in the Pythagorean Theorem material. The ability to think creatively is the ability that students have to solve problems in problems in a different, unique way or have never been found by others. In this study the method used is a qualitative research method. The subjects in this study were 3 students of class VIII. The level of creative thinking ability is divided into 3 namely, creative, less creative, and not creative. Data collection was carried out by providing 4 questions on the Pythagorean theorem material which contained indicators for assessing creative thinking abilities, namely fluency, flexibility, originality, and detail. In this study, it was found that 1 student had the ability to think creatively, and 2 student had the ability to think less creatively.Keywords: Creative Thinking Ability, Phytagorean Theorem